PENGEMBANGAN MEDIA PEMBELAJARAN MINIATUR DENAH LOKASI TEMA 3 SUBTEMA 1 KELAS II SEKOLAH DASAR - Rafise Oktiama Lestari; Muhammad Prayito; Fine Reffiane (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to: (1) develop media using miniature site plans in grade II elementary schools (2) determine the feasibility of developing miniature site plan learning media. This research is a type of Research and Development (R&D) research with the ADDIE model which includes five steps including: analysis, design, development, implementation, evaluation. The subjects in this study were media expert validators, material experts, and second grade elementary school students. The research instruments used in data collection were questionnaires, observations, interviews and documentation. The results of this study indicate that the learning media for Miniature Floor Plans for Class II Elementary Schools are "Very Eligible" with details on the eligibility percentage given by media experts yielding 97.5% "Can Be Used Without Revision". Then Material experts produce 100% "Can be Used Without Revision" . The results of the student response questionnaire obtained an average percentage of 94.1% with the "Very Good" criteria. Therefore it can be concluded that the learning media for Miniature Floor Plans for Class II Elementary Schools can be used well for students during the learning process in class II Elementary Schools.